The connection between hydrothermal fluids, mineralization, tectonics and magmatism in a continental rift setting: Fluorite Sm-Nd and hematite and carbonates U-Pb geochronology from the Rhinegraben in SW Germany. (1st November 2018) - Walter, Benjamin F.; Gerdes, Axel; Kleinhanns, Ilka C.; Dunkl, István; von Eynatten, Hilmar; Kreissl, Stefan; Markl, Gregor
Abstract: Understanding the physical basics of tectonic events, related fluid flow and ore deposition represents one of the great challenges in modern geosciences. In this contribution, Sm-Nd ages of hydrothermal fluorites and U-Pb ages of carbonates and iron oxides from unconformity-related vein type deposits in the Schwarzwald next to the Upper Rhinegraben rift in SW Germany are used to distinguish different pulses of hydrothermal fluid activity and to understand their relation to large-scale tectonics and magmatism. While the fluorites are of Early Jurassic to Oligocene age, carbonate (calcite, dolomite, siderite) and hematite dated by U-Pb small-scale isochrons records formation from Permian to Quaternary with a clear culmination in the Neogene. These new age-data in combination with microthermometry data of primary fluid inclusions from growth zones in the fluorites and carbonates are used to constrain the timing of fluid signatures. This contribution shows that the ages are correlated with changes in fluid properties and/or tectonic events in the evolving continental crust. Comparison with published thermochronological data, apparent ages of URG-related volcanic rocks and the tectono-sedimentary evolution of the Upper Rhinegraben rift show clear correlations between the intensity of hydrothermal mineralization (and, hence, the intensity of fracture-bound fluid flow) with the U-Pb carbonate ages. This method accordingly provides an excellent tool to date rift-related processes like fluid flow, ore deposition and tectonic activation or reactivation of fractures. Fluid properties changed after the deposition of Middle Triassic Muschelkalk evaporites from low salinity, high temperature (1–6 wt.% NaCleq, 200–270 °C, cooling late-metamorphic basement fluids) to high salinity, moderate temperature (20–26 wt.% (NaCl + CaCl2 ), 50–170 °C, mixture of a modified bittern brine ("basement brine") with halite dissolution brine). This change led to large scale ore deposition (fluorite-barite-quartz with Pb-Zn-Cu, Bi-Co-Ni-Ag-U, Fe-Mn ores). During the Paleogene and Neogene, previously separated aquifers from various sedimentary units were connected by juxtaposition of the fluid source rocks during Rhinegraben rifting, which resulted in variable salinity and temperature fluids (1–26 wt. % (NaCl + CaCl2 ), 50–350 °C) by a multi-component fluid mixing process. Typical mineralization related to this shows barren or Pb-Zn-Cu veins with large amounts of barite.